Conservation of a functional hierarchy between mammalian and insect Hox/HOM genes. - Bachiller, D (EMBO J, 1994)
We have generated several transgenic Drosophila strains containing different mouse Hox genes under heat shock control and studied how their generalized expression affects Drosophila larval patterns. We find that they have spatially restricted effects which correlate with their genetic order and expression pattern in the mouse; as they are expressed more posteriorly in the mouse, they have more extensive effects in Drosophila. The generalized expressions of Hoxd-8 and d-9 modify Drosophila anterior head segment(s), but have no effect in the rest of the body. Hoxd-10 expression affects head and thorax, but not the abdomen. Finally, Hoxd-11 alters head, thorax not the abdomen. Finally, Hoxd-11 alters head, thorax and abdomen. The developmental effect of the Hox genes consists of a homeotic transformation of the affected segment(s), which exhibit a 'ground' pattern similar to that obtained in the absence of homeotic information, suggesting that Hox genes are able to inactivate Drosophila homeotic genes, but do not specify a pattern of their own. A partial exception is Hoxd-11 which, even though it has a general suppressing effect, can also activate the resident Abdominal-B and empty spiracles genes in ectopic positions. Our results strongly suggest a general conservation of the functional hierarchy of homeotic genes that correlates with genetic order and expression patterns. IMAGES: